Sklepy internetowe - doskonalenie obsługi klientów - Iwankiewicz-Rak, Barbara (E-commerce - Improvement Customer Services, 2008)
The paper presents growth of e-commerce in Poland in comparison to other countries. It shows e-shops functioning rules and classification criteria. The author also presents commonly used payment methods and protection programmes implemented in order to increase safety of buying and account protection. The paper concludes with an analysis of success factors for e-shops.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 138-150